Examining the Role of Indonesia's Constitutional Court as a Positive Legislator: Menelaah Peran Mahkamah Konstitusi Indonesia sebagai Legislator Positif - Fikriya, Makhyatul; Sulastri , Dewi; Kania, Dede; Rizqia, Rania Nurul (Rechtsidee, 2024)
The judicial review process is pivotal in democratic governance, ensuring laws align with constitutional mandates. Constitutional Court Decision Number 90/PUU-XXI/2023, addressing amendments to Article 169, letter q of Law Number 7 of 2017 on Elections, has generated significant legal discourse. This study aims to analyze the legal dynamics within this judicial review, employing a descriptive-analytical methodology with a comparative approach. This involves comparing legal systems across different countries to understand the Constitutional Court's controversial role. Traditionally, the court's authority lies in acting as a negative legislator; however, in this case, it has taken on a role akin to a positive legislator, creating potential conflicts with the legislative body. The findings indicate a debate over the court's authority to add norms, revealing a fundamental tension between the judiciary and legislative functions. This decision introduces new legal implications, highlighting the necessity for further analysis to ensure the realization of substantial democracy. The study fills a knowledge gap by providing a comprehensive analysis of the court's expanded role, proposing solutive mechanisms to address the emerging legal challenges and maintain a balanced power dynamic between the judiciary and the legislature. This research underscores the importance of clear delineation of judicial and legislative responsibilities to uphold democratic principles. Highlights: The court's controversial role in amending election law norms. Debates over the court's authority and legislative implications. Need for solutions to maintain democracy and balance of power. Keywords: Judicial Review, Positive Legislator, Constitutional Court, Legal Authority, Democracy